Temporal change in resident perceptions of a mega-event: The Beijing 2008 olympic games - Gursoy, D; Chi, C.; Ai, J.; Chen, B. (2011)
Abstract This study investigated the influences of temporal effects on local residents' impact perceptions of hosting the Beijing 2008 Olympic Games, utilizing data collected during the first week of the games and after the games from local residents of Beijing. Findings suggested that thirteen of the 30 impact items examined were significantly different between the assessment of impacts during and after the games. While changes in two of those impact perception items indicated that residents' perceptions changed for the better after the games, eleven of them suggested that during the first week of the games residents had high expectations about the benefits, though they were aware that such benefits would not be cost-free. However, they later realized that the benefits generated were lower than they had anticipated and the costs associated were higher than they expected. © 2011 Taylor & Francis.